Analysing the Effectiveness of the Legal Framework on Access to Education for Children in Uganda - Mary Ipadut (Uganda Christian University, 2024)
The study analyzed the effectiveness of legal framework on access to education for children in Uganda, the study reveals that despite the legal framework, many children still face challenges in accessing education, including poverty, lack of infrastructure, and inadequate resources. The government has a critical role to play in ensuring that all children have access to education, and parents and guardians also have a role to play in ensuring that children attend school and participate in educational activities. The legal framework in Uganda provides a solid foundation for promoting access to education for all children, based on principles of equality, non-discrimination, and the best interests of the child. However, many children still face challenges in accessing education due to poverty, lack of infrastructure, and inadequate resources. Education is a fundamental human right essential for the development of children and the country. It provides skills, knowledge, and values necessary for success and promotes social mobility, economic growth, and development. Despite the legal framework, many children face challenges in accessing education, including poverty, lack of infrastructure, inadequate resources, and cultural and social barriers. Rural and poor children are particularly affected. The government has a critical role in providing infrastructure, teachers, and resources necessary for education. Parents and guardians also have a critical role in ensuring children attend school and participate in educational activities. However, many parents and guardians are unable to fulfill their duties due to poverty, lack of education, and inadequate resources. Th study recommended Increase funding for education to address challenges and limitations that prevent children from accessing education, allocate a minimum of 20% of the budget to education, as recommended by the African Union, provide support to parents and guardians to enable them to fulfill their duties in ensuring children attend school and participate in educational activities.